Key techniques of creating art reality in the ecological novel of a new type «Lead your plouch over the bones of the dead» by Olga Tokarchuc (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
In the article techniques are investigated with the help of which Olga Tokarchuk's author's strategy is realized in the novel “Lead your plough over the bones of the dead” which can be determined as “an ecological novel of a new type” since besides ecological problems of moral character are raised and solved in it. It is stressed that Olga Tokarchuc's characteristics of creative individuality is the masterful using of text characters that are attractive to the readership, such as a special heroine, corresponding to the type of trickster demanded in modern literature; a series of mysterious deaths; opposition to the forces of evil, etc. Such authorial strategies contribute to building the text as a multi-genre structure, for which both the external series of events and the hidden semantic plan are equally important.It is noticed that the artistic reality in the novel Tokarchuk was created using a variety of techniques: switching attention from particular to general and vice versa; paradox; constant change of angle and scale. Core techniques for Tokarchuc's creative tactics are typical rhizome genre strategy, subjective author's modality, an accent on paratextual components of the text are revealed.Because of such a strategy, Tokarchuk realized an ecological novel in a new form, the classic example of which is “Roots of Heaven” by Romain Gary, outlined to contemporaries global goals: to protect the ideals and values of humanism, saving nature. For Olga Tokarchuk’s novel, it’s important that the problem of nature protection develops into an ecology of morality, exposing the question of the permissibility of murder, practically crime and mob law, as a way to fight for the rights of animals or defenseless people, similar to the heroine of the novel against those whom the writer calls "hunters." Art reality is depicted in Tokarchuк's novel with projection in metaphysical senses and, therefore, it allows to talk about the theme of ecological of a moral feeling.
Keywords: an ecological novel; a technique; author's modality; rhizome genre strategy; elements of paratext